A disaster warning model for a spacecraft launch based on information fusion and network inference. (1st January 2012) - Xuejun, Dong; Yingwu, Chen; Jianwei, Ma; Ming, Li
The launch of spacecraft should synthesise various incomplete and uncertain symptoms of extreme events to dynamically assess the possibility of disaster during the launch readiness process. However, there are still many technical problems in disaster assessment of spacecraft launch engineering. For example, the problem of how to effectively use the disaster symptoms is not addressed well yet and the fact that group decision-making can be easily lead to the minority opinion being ignored. Based on the extreme event symptom obtaining technique, a disaster warning model combining both virtual and real evidence is built through information fusion and network inference, using evidence theory and Bayesian theory. Using information fusion, the proposed model shows good performance with regard to complementary evidence, elimination of data redundancy and reduction of uncertainty. Using symptom information-based network inference, this model guarantees the identification of the correct minority. Finally, the effectiveness, correctness and feasibility of the model are verified by analysis of the 'Challenger' space shuttle explosion.